The sound of gravel [compact disc, unabridged] : a memoir - Wariner, Ruth (Macmillan Audio, 2016)
Ruth was the 39th of her father's 41 children in a polygamist doomsday cult. When she was only a few months old, Ruth's father-- the man who had been the founding prophet of the community-- was brutally murdered by his brother in a bid for church power. Ruth's mother remarried, becoming the second wife of another faithful congregant. Ruth's mother gave birth to six more children. Ruth and her siblings were carted back and forth between Mexico and the United States, where her mother collected welfare and her stepfather worked odd jobs. Ruth came to love the time she spent in California and Texas, but as she entered adolescence, her stepfather began seeking her out, forcing her to sit on his lap, touch him, and endure his molestation. Try as she might, Ruth could not persuade her mother or church elders to question her stepfather. Finally, and only after devastating tragedy, Ruth found an opportunity to escape. The remarkable true story of a girl forced to define her own faith.